Reference limits of five major reproductive hormones for some Ghanaian women of child bearing age - Martey, Georgina Naa-Oye (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Chemical Pathology.